2021
DOI: 10.3390/fluids6110408
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a Mask and Its Performance Analysis with CFD for an Enhanced Aerodynamic Geometry That Facilitates Filtering and Breathing against COVID-19

Abstract: As a result of the recent events associated with the SARS-CoV-2 around the world, there has been a need for research to strengthen health care. The use of masks or respirators has been an effective measure, reducing the risk of contagion caused by the spread of the virus in public places. Currently, there are masks that retain up to 99% of particles >0.3 microns; however, they lack an airtight seal with the face, leading to discomfort and poor protection in conditions without social distancing and areas wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Furthermore, amongst different activities to evaluate the fit factor of different masks; talking has a greater effect on reducing the overall fit factor for the sealed surgical masks than for the N95 mask. To address the fitting issue of masks, López‐Rebollar 69 designed a mask using valves and deflectors inside the mask. Through CFD analysis, they found that the exhaled air flow had a long time and recirculation path within the mask before exiting.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, amongst different activities to evaluate the fit factor of different masks; talking has a greater effect on reducing the overall fit factor for the sealed surgical masks than for the N95 mask. To address the fitting issue of masks, López‐Rebollar 69 designed a mask using valves and deflectors inside the mask. Through CFD analysis, they found that the exhaled air flow had a long time and recirculation path within the mask before exiting.…”
Section: Resultsmentioning
confidence: 99%
“…CFD enables the analysis of gas phase and particle contaminant concentration distributions in two-phase flows, as well as particle deposition [10]. The significance of IAQ, both in industrial and general settings, has become increasingly evident during the current pandemic, along with the numerous health risk assessments associated with the novel human coronavirus SARS-CoV-2 [11][12][13][14][15][16]. By leveraging CFD tools to study aerosol and particle dispersion, researchers have gained insights into the effective control and management of industrial indoor air quality.…”
Section: Introductionmentioning
confidence: 99%